The shape of the association between income and mortality in old age: A longitudinal Swedish national register study - Johan Rehnberg; Johan Fritzell (Elsevier, 2016)
This study used data on the total population to examine the longitudinal association between midlife income and mortality and late-life income and mortality in an aging Swedish cohort. We specifically examined the shape of the associations between income and mortality with focus on where in the income distribution that higher incomes began to provide diminishing returns. The study is based on a total Swedish population cohort between the ages of 50 and 60 years in 1990 (n=801,017) followed in registers for up to 19 years. We measured equivalent disposable household income in 1990 and 2005 and mortality between 2006 and 2009. Cox proportional hazard models with penalized splines (P-spline) enabled us to examine for non-linearity in the relationship between income and mortality. The results showed a clear non-linear association. The shape of the association between midlife (ages 50-60) income and mortality was curvilinear; returns diminished as income increased. The shape of the association between late-life (ages 65-75) income and mortality was also curvilinear; returns diminished as income increased. The association between late-life income and mortality remained after controlling for midlife income. In summary, the results indicated that a non-linear association between income and mortality is maintained into old age, in which higher incomes give diminishing returns. Keywords: Income, Health inequality, Mortality, Old age, Late-life, Non-linear, Diminishing returns, Sweden